Multicultural counseling : perspectives from counselors as clients of color - Marbley, Aretha Faye (Routledge, 2011)
This is the first book to explore the experiences of people of color in counseling from the perspective of individuals who are practicing counselors and were previously clients in counseling themselves. Marbley conducted a research study in which she interviewed eight individuals representing each of the major groups of color in the United Statesu?African American, Asian and Asian American, Hispanic/Latino, and American Indianu?to obtain the stories of their experiences in their own words. These stories provide insight into the problems and failures of counseling services provided to people of color. She quotes extensively from these interviews throughout the book, using the voices of the participants to highlight these shortcomings and personalize her discussion of the issues they have faced. A chapter is devoted to each of the groups of color, as well as one to counseling issues related to gender. These chapters provide an overview of the literature on the historical experiences of these groups in mental health and a discussion of the counselors' experiences, and conclude with implications and recommendations for counseling and psychotherapy with these groups. Information from follow-up interviews conducted 12 years after the original ones is also provided to compare and contrast the participants' responses to their earlier ones. Marbley concludes with a look at the need for a social justice movement within the mental health field in order to improve the experiences of and outcomes for people of color